Uji Toksisitas Akut Ekstrak Daun Kamboja (Plumiera rubra L.) pada Ikan Nila Merah (Oreochromis niloticus) Acute Toxicity Test Extract Frangipani Leaves (Plumiera rubra L.) on the Red Tilapia (Oreochromis niloticus) - Rangga Warsito; Yunasfi Djayus; Zulham Apandy Harahap (AQUACOASTMARINE, 2015)
Aquaculture is done highly intensive susceptible to outbreaks of diseas. The use of antibiotics in the prevention of bacterial diseases can cause negative effects to human health. Antibiotics can be replaced with the use of plant extracts containing antibacterial compounds, one of which frangipani leaves (Plumiera rubra L.). This study aims to determine the 96-hour LC50 value and safe concentration of frangipani leaf extract of red tilapia fish seeds. The study is divided into two stages, namely the preliminary test and the definitive test. Preliminary test was conducted to determine threshold concentrations above and below the threshold, where the concentration of the preliminary test is 0 ppm, 50 ppm, 100 ppm, 200 ppm, and 750 ppm. Definitive test using a concentration of 0 ppm; 98,40 ppm; 193,65 ppm; 381,10 ppm; and 750,00 ppm were obtained from calculations based on the threshold concentration of 750 ppm and below the threshold of 50 ppm. Percentage mortality of red tilapia in a preliminary test of the lowest to highest concentration of 3,33%; 16,67%; 46,67%; and 76,67%. Percentage mortality converted into the form used in the probit and probit analysis to obtain the 96-hour LC50 value of 510,63 ppm. Safe concentration of 10% of the LC50 within 96 hours, which is 50,2 ppm. In the 96-hour LC50 valuesindicate that the extract of frangipani leaf included in the category of moderate toxicity.Keywords : Plumiera rubra L., Oreochromis niloticus, LC50, phytochemistry